Domestic Tourist Market in the Population Estimates: A Sociological Analysis - FROLOVA, Elena Victorovna; ROGACH, Olga Vladimirovna; KABANOVA, Elena Evgen'evna; RYABOVA, Tatyana Mikhailovna (Journal of Environmental Management and Tourism, 2017)
This article is devoted to the assessment of satisfaction among different social groups with the tourism service rendered within the framework of cultural and educational trips over Russia. This work is based on the results of the investigations of the Russian Public Opinion Research Center (WCIOM), the Public Opinion Foundation (FOM). As the main research method we have chosen questionnaire which has allowed us to reveal preferences of the tourists from different social categories. This questionnaire is based on the main components forming tourists’ satisfaction with the trips over Russia. In the course of the mentioned-above investigation we have found dependence between the number of the trips in different cities and towns of Russia, and the level of satisfaction with the quality of the tourist service of the domestic tourism industry. The authors have conducted analyses of the main problems with which tourists usually encounter while travelling over the country. These problems include the following aspects: lack of well-developed tourism infrastructure in the Russian cities and towns, dissatisfaction with variety of animation programs, most part of package tours does not render efficient full service. At the same time, we can conclude that increasing number of the Russians acknowledge the historic and cultural importance of the cities heritage. They assess the level of arrangement of the holidays, entertainments as a quite high. Almost a half of the respondents gave positive assessment to the level of satisfaction with such tourism service as the level and quality of traditional folk craft, an opportunity to immerge into the history and culture of a region, contribute to the revival of cultural values.